Collaborative Governance in Overcoming Unemployment in Tangerang Regency - Andini, Nunung; Cadith, Juliannes; Maisaroh, Ima (SEAN Institute, 2023)
The problem of unemployment is a big and serious problem in Indonesia, including in Tangerang Regency. Unemployment occurs because the number of job seekers is greater than the number of jobs. However, in reality, Tangerang Regency actually has the most employment opportunities or industry, as well as the unemployment rate, resulting in an imbalance of resources. Presidential Decree No. 4 of 1980 regarding the obligation to report job vacancies is still not implemented properly, so the Tangerang Regency Manpower Office implements Regional Regulation No. 12 of 2016 concerning employment which is obliged to organize job training and FKLPID forums in its collaboration. In this case, it was found that there was no community involvement in the forum and there was a lack of participation by industrial companies in the job training program so that a sense of dependency in collaboration had not been formed. Republic of Indonesia Banten Representative in Handling Maladministration Reports. The method used in this research is qualitative with a purposive informant selection technique. The theory used is the Ansell and Gash collaboration model, namely: initial conditions, institutional design, passive leadership, and collaboration processes. Data collection techniques include observation, interviews and documentation. Data validity testing uses triangulation and member check. The results of this research are that collaboration in overcoming unemployment in job training programs is not optimal, this can be seen from the lack of company participation, trainer resources, and community involvement in forums.